Surgical strategies in pediatric supracondylar humeral fractures: our experience - Maccagnano, Giuseppe; Noia, Giovanni; Coviello, Michele; Stigliani, Costantino; Cassano, Giuseppe Danilo; Dibello, Daniela; Pesce, Vito; Moretti, Biagio (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Supracondylar humeral fractures are the most common skeletal injury of childhood elbow. Treatment option for Gartland type II-III-IV fractures is based on closed reduction and percutaneous pinning (CRPP) fixation using Kirshner wires. Seldom open reduction is needed. Literature described different method of CRPP. The aim of the study is to report our experience in the surgical management of supracondylar humeral fractures comparing it with the literature, in order to identify useful information for a correct and better approach to reduce complications and improve clinical outcomes. Methods: 148 patients with a mean age of 5.72 ± 2.52 years and with Gartland type II-III-IV humeral supracondylar fractures were treated with CRPP at our Orthopedic Pediatric Unit. They were divided into three groups according to surgical technique. Group A was represented by patients treated with cross pinning (1 medial and 1 lateral pin), Group B represented by 2 lateral pins while Group C represented by 2 lateral and one medial pin. Evaluation criteria are based on Mayo Elbow Performance Index (MEPI); Bauman’s and Carrying Angle and Flynn's criteria. Data were recorded at the following times: T0 (before surgical procedure); T1 (one-month post-surgery); T2 (six months post-surgery). Results: The three surgical techniques showed comparable results according to MEPI, Bauman’s angle, Carrying’s angle and Flynn's criteria from T0 to T1. There is an improvement for all Groups. Group C reported the best MEPI outcome at T2. However, 2 patients in this group did not show excellent results according to Flynn's criteria.Conclusions: There is no single and superior treatment for displaced humeral supracondylar fractures and that each fracture has its own personality.